HUBUNGAN ANTARA MENJAGA KEKUDUSAN DALAM PERNIKAHAN KRISTEN DENGAN PERTUMBUHAN ROHANI JEMAAT GPT BINTANG FAJAR BALI - Santoso Tiwan; Fanny Jermia; Ermin Hidayati (Sekolah Tinggi Teologi Pelita Hati, 2026)
The sanctity of Christian marriage serves as the foundation of spiritual life. Therefore, maintaining sanctity in Christian marriage has a significant impact on spiritual growth and a positive influence on the congregation as a whole. A holy marriage can serve as a model for other members of the congregation, encouraging them to uphold Christian values in their own marriages. This study illustrates how maintaining sanctity can foster a healthy relationship with God. This strengthens their bonds with the congregation and the church community, as they become more active in church activities and ministry. The sanctity of Christian marriage also has a profoundly positive impact on the spiritual growth of children. Children raised in families that uphold the sanctity of marriage tend to grow up with a strong spiritual foundation. This significantly contributes to their spiritual growth and, ultimately, to the spiritual growth of both the individual and the congregation as a whole. The method used in this study is a qualitative approach, with data collection conducted through literature review and brief interviews via a questionnaire. In addition, the researcher also used several instruments such as questionnaires, observations in the form of home visits to congregation members, interviews during premarital and post-marital counseling, and interviews with informants who possess expertise and experience related to the research topic